Evaluation of toxicity profile of kratom (Mitragyna speciosa Korth) decoction in rats - Hassan, Zurina; Singh, Darshan; Suhaimi, Farah Wahida; Chear, Nelson Jeng-Yeou; Harun, Norsyifa; See, Cheah Pike; Kaur, Gurjeet; Mat, Noorul Hamizah; Bakar, Siti Najmi Syuhadaa; Mohd Yusof, Nur Sabrina; Kasinather, Vicknasingam Balasingam; Chawarski, Marek C.; et al. (Academic Press Inc., 2023)
Mitragyna speciosa Korth also known as kratom, is an herbal drug preparation for its therapeutic properties and opioid-replacement therapy. Kratom is consumed in a brewed decoction form in Malaysia and to date, no studies have characterized its chemical and toxicity profile. Thus, this study aims to evaluate kratom decoction's safety and toxicity profile after 28 days of treatment. Mitragynine content was quantified in kratom decoction and used as a marker to determine the concentration. Male and female Sprague Dawley rats were orally treated with vehicle or kratom decoction (10, 50 or 150 mg/kg) and two satellite groups were treated with vehicle and kratom decoction (150 mg/kg). Blood and organs were collected for hematology, biochemical and histopathology analysis at the end of treatment. No mortality was found after 28 days of treatment and no significant changes in body weight and hematology profile, except for low platelet count. High amounts of uric acid, AST, ALT and alkaline phosphatase were found in the biochemical analysis. Histological investigation of the heart and lungs detected no alterations except for the kidney, liver and brain tissues. In conclusion, repeated administration of kratom decoction provided some evidence of toxicity in the kidney and liver with no occurrence of mortality.